Association of the use of psychotropic drugs with hospitalization, cardiovascular events, and mortality in patients with type 2 diabetes: a propensity score-matched cohort study - Hamasaki, Hidetaka; Yanai, Hidekatsu (Frontiers in Clinical Diabetes and Healthcare, 2023)
Background: Use of psychotropic drugs (PD) may be associated with impairment of physical function. However, few studies have assessed the impact of PD on health outcomes in patients with type 2 diabetes. This study aimed to examine the associations between psychotropic drug use and handgrip strength (HGS) and between the use of PD and hospitalization in patients with type 2 diabetes. Methods: From April 2013 to December 2015, we conducted a retrospective cohort study in patients with type 2 diabetes at our hospital. Nonpsychotropic drug users were matched one-to-one with the PD users using propensity score matching method with respect to their baseline covariates. The differences in HGS and the number of patients who had hospitalizations during the study period were examined. By Kaplan–Meier survival analysis, the association between the use of PD and multiple hospitalizations was estimated. Results: A total of 1,282 patients were enrolled and followed up for 2.36 ± 0.73 years. In the propensity score matching cohort, HGS was significantly lower (p = 0.006) in PD users than non-PD users. PD users had more hospitalizations than non-PD users. Survival curves confirmed the association of multiple hospitalizations with the use of PD (p = 0.015). In addition, HGS was significantly and inversely correlated with the number of hospitalizations (r = −0.143, p = 0.013). Conclusions: The use of PD could increase the risk of multiple hospitalizations. Skeletal muscle may play a role in reducing the risk of hospitalization in patients who are treated with PD.